Technology in Music Education - Maharaj, Adita; Gill, Akini (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2023)
This study examined the use of music software as a pedagogical tool for the delivery of specific content in a music education course offered to Certificate and Bachelor of Education Program students at a Caribbean university. The existing course uses a traditional approach, and thus, the study is significant as the results would propel a shift toward transformational teaching. Twenty-four university students were chosen for the study which adopted a mixed methods approach. Over one semester, participants used a free, open-source music software program to learn simple time signatures. Students produced an assignment as well as completed a questionnaire. Ninety percent of students were able to compose eight bars of music according to a simple time signature using the software. Most participants intimated they felt comfortable and motivated using the software, they understood concepts taught, and they suggested its continued use. The majority of participants also stated that they required more training. Some participants even said that they would adopt this methodology on their teaching practicum. Based on the results, recommendations include the adoption of this and other technological teaching tools within the music program, a teaching practicum assessment, and a progressive training component for both students and staff.